STRATEGIES USED BY UNDERGRADUATE ENGLISH-MAJORED STUDENTS IN ORAL COMMUNICATION - Tuyen, Le Van; An, Huynh Thi; Hong, Tran Kim (VNU Journal of Foreign Studies, 2020)
Communication strategies (CSs) play a significant role in enabling EFL students to achieve a higher level of English proficiency and good ability in oral communication. Helping both EFL teachers and students be aware of CSs is essential in the Vietnamese context. This study, therefore, aimed to explore the most commonly used strategies in English oral communication among English-majored students at Ho Chi Minh City University of Technology (HUTECH)-Vietnam. Two instruments were employed to collect both qualitative and quantitative data, namely (1) the questionnaire and (2) the focus group with the participation of 213 English majored sophomores, juniors and seniors. The findings of the study revealed that the most commonly-used speaking strategies are ‘fluency-oriented’, ‘message reduction and alteration’, and ‘negotiation for meaning while speaking’, and that the students used achievement strategies more often than reduction ones; and the most commonly-used listening strategies are ‘negotiation for meaning while listening’, ‘non-verbal’ and ‘scanning’. The findings also revealed that there are no significant differences in the use of CSs among the three academic levels of students. It is expected that the findings of the study would partly contribute to the enhancement of communicative competence (CoC) and the use of CSs among students at HUTECH in particular and at the Vietnamese tertiary level in general.